Argumentation and Appraisal in Parliamentary Discourse - Ernest Jakaza (IGI Global, 2023)
Political debates have reached unprecedented levels of interest around the globe as more individuals begin to comprehend government proceedings and discourse. Utilizing this knowledge, individuals are becoming attentive to political language, but they lack information on the motivation behind it. Argumentation and Appraisal in Parliamentary Discourse seeks to interrogate the argumentation practices and appraisal forms realized in parliamentary discourse on various topics. While highlighting topics that include legislative immunity, political rivalry, and language evolution, it features crucial discourse-pragmatic research on parliamentary proceedings from various parliamentary settings. This book is recommended for linguists, politicians, professionals, and researchers working in the fields of discourse analysis, linguistics, politics, communication sciences, sociology, and conversational analysis.